Our Search for Intergenerational Rhythms as Tongan Global Scholars - Faleolo, Ruth (Lute); Fehoko, Edmond; Dyck, Dagmar; Hafu-Fetokai, Cathleen; Malungahu, Gemma; Clark, Zaramasina L; Hafoka, Esiteli; Tovo, Finausina; Taufui Mikato Fa‘avae, David (Art/Research International, 2024)
Our search for collective meaning-making across spaces and places as Tongan global scholars carries intergenerational rhythms. This article is a diasporic collaboration between members of the Tongan Global Scholars Network (TGSN), an online cultural collective drawn together through creatively critical rhythms and a desire to make space for ongoing criticalities through Tongan concepts, knowledge, and approaches. Employing the art of e-talanoa in our search for ways of crafting meaning, we unfold our narratives about TGSN’s humble beginnings using a range of modalities expressed as words, images, screenshots, and poetry. Our desire to connect early career scholars of Tongan heritage across the diaspora of Australia, the United States of America, Aotearoa New Zealand, and Tonga via the online space, led to enabling intergenerational relational rhythms between more seasoned and emerging scholars, sharing their understanding of Tongan knowledge and its relevance in the dominant Western academe. Intergenerational rhythms are central to TGSN’s survival. As a global network, TGSN continues to provide meaningful spaces for creatively critical meaning- making and intergenerational collaborative dialogue.